Reduction of Faults due to Preventive Maintenance Non-compliance in Pakistan’s Glove Sector using DMAIC Approach: Faults reduction due to Maintenance Non-compliance - Majid, Muhammad Imran; Hashmi, Muhammad Raza; Gill, Josh Bekashah (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this era, the Pakistani glove manufacturing companies are striving for higher operational efficiencies to meet the forecasted demands of US1.25 billion in Asia by 2025. Endeavouring for excellence these companies are hampered by limited operational efficiencies due to poor compliance of scheduled preventive maintenance (PM). Affected equipment encounters numerous faults and as a result a higher unplanned downtime. This paper aims to reduce such faults using DMAIC (Define, Measure, Analyse, Improve and Control) approach on a glove manufacturing equipment. Applying DMAIC, the analysis indicated that a fault “Former linkage assembly issue” contributed 33.3% of total recurring faults, 34% of total unplanned downtime. The Root cause for this fault namely “loosening and plays in former linkage assembly” was diagnosed by the project team for possible remedies. An experimental analysis carried out during the noncompliance period identified that increasing the frequency of a remedial task for this root cause “tightening and adjustment in linkage assembly” from 5 days to 2 days resulted in an increase in equipment OEE increase from 75.85% to 77.15%. This along with other improvement tasks was incorporated practically as well as in the company`s CLIT (cleaning, lubrication, inspection, and tightening) sheet, and SOP was created. These improvements will lead to a reduction of faults during future cases of PM noncompliance events. This paper certainly adds value for glove sector engineers to imply similar process improvement approaches in their companies to reduce chronic faults recurrences and maximize the operational efficiency under PM noncompliance situations.